Doping Effect of Fe on Some Physical Properties of Y156 Superconductor Synthesized by Solid State Reaction - บุญโยประการ, วรายุทธ; สิรินิลกุล, สิริ; นิลกำจร, ธัญนพ; ตันติวิชิตเวช, กัญชพร; สุจินพรัหม, ศุภเดช; อุดมสมุทรหิรัญ, พงษ์แก้ว (Progress in Applied Science and Technology, 2018)
In this paper shown the result of Fe2O3 on YBa5(Cu1-xFex)6O24-y superconductors, when x is 0.001, 0.003 and 0.005 Wt%, were prepared by solid-state reaction. The calcination and sintering temperature were 900 ◦C. Both scanning electron microscope and energy dispersive X-ray spectrometer were used to analyze the characteristic properties of all samples. The electrical resistivity of the superconductor was measured between 77 to 120 K by four-point probe method and liquid nitrogen was used to cooling in the process. Researchers found the number of Fe2O3 in the superconductor affected to the superconducting state and the highest critical temperature was discovered at 94.8 K.